Self Compassion dan Kualitas Hidup Profesional Perawat selama Pandemi COVID-19 - Juniarta Juniarta; Idem Suarni Gea; Wahyu Shisilia Lalenoh; Yunira Elsa Vinolita Tatontos; Novita Susilawati Barus (Jurnal Keperawatan Padjadjaran, 2023)
Background: Self-compassion enables nurses to understand, know, and love themselves when faced with challenges, specifically during the COVID-19 pandemic. It will decrease compassion fatigue and raises compassion satisfaction. Purpose: This study aimed to test how nurses’ self-compassion related to their professional quality of life (compassion satisfaction, burnout, and secondary traumatic stress) during the COVID-19 pandemic in Indonesia. Methods: This was a quantitative correlational study which recruited 234 nurses from all over Indonesia using convenience sampling technique. To collect data, an online survey was administered. Descriptive statistics and the Spearman rank test were used to analyze the collected data. Results: Self-compassion and compassion satisfaction have been found to have significant relationships (p=0.718), likewise self-compassion and burnout (p=0.726), and self-compassion and secondary traumatic stress (p=0.516). Conclusions: Self-compassion increases compassion satisfaction. When nurses care for themselves, compassion fatigue (burnout and secondary traumatic stress) will be reduced, and vice versa. Self-awareness is required for nurses to cultivate self-compassion by focusing on and accepting each live event without regret.